Pengaruh Kepuasan Kerja, Dan Motivasi Terhadap Kinerja Karyawan Dengan Komitmen Organisasi Sebagai Variabel Intervening Pada PT Antar Lintas Sumatera-Medan - Kiki Mirella; Chintya Ones Charli; Nurul Raudah A.M; Nada Absilah Salsabila (Universitas 45 Surabaya, 2024)
This study's goal is to analyze the impact of job satisfation and motivation on employees' work and organizational commitment as an intervening variable in a sample of 35 from PT Antar Lintas Sumatera-Medan. The study's type is explanatory research. The data collection method uses a survey with a questionnaire that is given to the respondent. The Smart PLS method.